The New Era of Treatment for Obesity and Metabolic Disorders: Evidence and Expectations for Gut Microbiome Transplantation - Jayasinghe, Thilini N.; Chiavaroli, Valentina; Holland, David J.; Cutfield, Wayne S.; O'Sullivan, Justin M. (Frontiers in Cellular and Infection Microbiology, 2016)
Obesity has reached epidemic proportions. Despite a better understanding of the underlying pathophysiology and growing treatment options, a significant proportion of obese patients do not respond to treatment. Recently, microbes residing in the human gastrointestinal tract have been found to act as an “endocrine” organ, whose composition and functionality may contribute to the development of obesity. Therefore, faecal/gut microbiome transplantation (GMT), which involves the transfer of faeces from a healthy donor to a recipient, is increasingly drawing attention as a potential treatment for obesity. Currently the evidence for GMT effectiveness in the treatment of obesity is preliminary. Here, we summarize benefits, procedures, and issues associated with GMT, with a special focus on obesity.